Lie as a Norm of Decency in Japanese Society - E. I. Bryukhova (Концепт: философия, религия, культура, 2023)
The topic of lies is of considerable interest in linguocultural analysis. The article discusses the role of lies in the language behavior of the Japanese in connection with the most important Japanese socio-cultural attitudes. Lying in Japanese culture is characterized as a social phenomenon without negative components. Japanese culture, which reflects the main features of traditional societies of the Far East, has its own special socio-cultural space with the dominant role of Shinto beliefs. Shinto is characterized by following the natural and traditional order of things and the absence of a firm scale of assessment of good and evil. Lies for the Japanese do not create a rejecting effect: they are not condemned harshly and are not punished and lying is not a source of internal experiences and torment. The morality of the Japanese is situational and intuitive, moral virtues are often replaced by a sense of shame, and the Japanese need to maintain harmony, so lies are allowed and accepted favorably. A lie is even necessary as an element of etiquette, polite (decent) behavior to preserve harmony in the group. The Japanese tend to behave relating to the surrounding group members, so the use of easy, inconspicuous, and kind lies may be caused by a specific situation, by the rules of group behavior. In addition, the Japanese are not characterized by the anguish of conscience, internal awareness of their guilt, or reasoning about immorality — the main motivating point for them is what others will say. And people around them will recognize it as acceptable and necessary. Lying is closely related to the concept of tatemae — an external model of behavior demonstrated before another person. A person, hiding behind a facade, under a mask, says what the listener wants to hear. That behavior seems a little insincere or duplicitous but is usually used to avoid conflict and ensure smooth social communication, rather than to trick or deceive. One who does not use the rules of tatemae may hurt the feelings of the person he or she is talking to or make the conversation unpleasant by revealing too much. Lying can take the form of polite and socially acceptable silence when the speaker hides his disagreement and true thoughts from the listener.